2014
DOI: 10.1002/hyp.10292
|View full text |Cite
|
Sign up to set email alerts
|

Radar rainfall uncertainty modelling influenced by wind

Abstract: Abstract:Radar-based estimates of rainfall are affected by many sources of uncertainties, which would propagate through the hydrological model when radar rainfall estimates are used as input or initial conditions. An elegant solution to quantify these uncertainties is to model the empirical relationship between radar measurements and rain gauge observations (as the 'ground reference'). However, most current studies only use a fixed and uniform model to represent the uncertainty of radar rainfall, without consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Nevertheless, detailed radar data information along with layer selection should be implemented in further analysis. Besides the relative humidity, other meteorological variables (such as wind, which have been investigated on wind-induced error) [Collier, 1999;Nešpor and Sevruk, 1999;Duchon and Essenberg, 2001;Mittermaier et al, 2004;Lack and Fox, 2007;Fortin et al, 2008;Lauri et al, 2012;Dai et al, 2013Dai et al, , 2015Dai and Han, 2014] may also play important roles in resulting in radar-gauge rainfall discrepancies. Dai and Han [2014] proposed a scheme in tackling wind effects on radar-gauge comparison and found that it could be helpful in radar rainfall adjustment to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, detailed radar data information along with layer selection should be implemented in further analysis. Besides the relative humidity, other meteorological variables (such as wind, which have been investigated on wind-induced error) [Collier, 1999;Nešpor and Sevruk, 1999;Duchon and Essenberg, 2001;Mittermaier et al, 2004;Lack and Fox, 2007;Fortin et al, 2008;Lauri et al, 2012;Dai et al, 2013Dai et al, , 2015Dai and Han, 2014] may also play important roles in resulting in radar-gauge rainfall discrepancies. Dai and Han [2014] proposed a scheme in tackling wind effects on radar-gauge comparison and found that it could be helpful in radar rainfall adjustment to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al . [] investigated how the radar rainfall uncertainties vary with the wind field through analyzing and comparing the characteristics of the generated uncertainty bands under different wind situations. It is concluded that the wind field plays a vital role in radar rainfall uncertainty and this uncertainty may propagate in the hydrological model and consequently contaminate the model output.…”
Section: Discussionmentioning
confidence: 99%
“…During the validation period, 45 rainfall events are selected as the test cases for the threshold's performances. To separate rainfall events from rainfall datasets, a one-day dry period (i.e., a period without rainfall) is used [49][50][51]. Since most of the landslides included in the datasets are shallow which respond quickly to rainfall, therefore a one-day approach is suitable here.…”
Section: Methodologiesmentioning
confidence: 99%